Strategi Manajemen Sumber Daya Manusia dalam Menghadapi Tantangan Industri Perkapalan - Muhammad Zaki Raihansyah; Choirul Ardiansyah; Izza Hanum Auliya; Laila Diana Puspita; Denny Oktavina Radianto (Journal Of Business, Finance, and Economics (JBFE), 2024)
The shipping industry faces increasingly complex challenges in the era of globalization and intense competition. The main issues faced include a shortage of skilled workforce, fluctuations in fuel prices, regulatory changes, and pressure to maintain environmental sustainability. This research aims to investigate effective human resource management (HRM) strategies to address these challenges. The research method utilized a literature review approach involving theoretical and empirical analysis from various relevant sources. The findings indicate that the implementation of HRM strategies focusing on skill development, recruitment and retention of workforce, and work-life balance has proven effective in enhancing productivity, employee retention, and financial performance of shipping companies. Additionally, the research reveals the importance of adaptability of shipping companies to changes in the business and technological environment, which can be achieved through leadership development and innovation promotion. These findings provide valuable insights for practitioners and researchers in understanding the dynamics of human resource management in the shipping industry and lay the foundation for the development of more effective strategies to address future challenges.